Peningkatan Keterampilan Bercerita Melalui Pendekatan SAVI Berbantuan Boneka Tangan - Yuniriang Waruwu (JURNAL GLOBAL EDUKASI, 2021)
Abstract: Based on initial data obtained through observations in Class II SD Negeri 076675 Ombolata Hilimbowo found problems in Indonesian language learning. The research objective was to improve teacher skills, student activities and student storytelling skills in Indonesian language learning. The research subjects consisted of teachers and students of Class II SD Negeri 076675 Ombolata Hilmbowo. Data collection techniques using test and non-test techniques. Data analysis techniques used qualitative and quantitative data. The results showed that the skills of the teacher in cycle I got a score of 24 with good criteria then increased to 29 with good criteria in cycle II. Student activity in cycle I got a score of 18.5 with sufficient criteria then increased to 24 with good criteria in cycle II. The storytelling skills of students in the first cycle got a score of 69.2 with classical completeness of 59% and the qualifications were not complete. The storytelling skills of students in cycle II increased to 76.1 with 88% classical completeness and complete qualifications. Key words: hand puppets; SAVI; storytelling Abstrak: Berdasarkan data awal yang didapatkan melalui observasi di Kelas II SD Negeri 076675 Ombolata Hilimbowo ditemukan permasalahan dalam pembelajaran bahasa Indonesia. Tujuan penelitian adalah meningkatkan keterampilan guru, aktivitas siswa dan keterampilan bercerita siswa dalam pembelajaran bahasa Indonesia. Subjek penelitian terdiri dari guru dan siswa Kelas II SD Negeri 076675 Ombolata Hilmbowo. Teknik pengumpulan data menggunakan teknik tes dan nontes. Teknik analisis data menggunakan data kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa keterampilan guru pada siklus I mendapatkan skor 24 dengan kriteria baik kemudian meningkat menjadi 29 dengan kriteria baik pada siklus II. Aktivitas siswa pada siklus I mendapatkan skor 18,5 dengan kriteria cukup kemudian meningkat menjadi 24 dengan kriteria baik pada siklus II. Keterampilan bercerita siswa pada siklus I mendapatkan nilai 69,2 dengan ketuntasan klasikal 59% dan kualifikasi tidak tuntas. Keterampilan bercerita siswa pada siklus II mengalami peningkatan menjadi 76,1 dengan ketuntasan klasikal 88% dan kualifikasi tuntas. Kata kunci : bercerita; boneka tangan; SAVI.